Pengaruh Ekspor, Impor, Kurs Nilai Tukar Rupian, Dan Tingkat Inflasi Terhadap Cadangan Devisa Indonesia Periode 1999-2018 - I Putu Agung Baskara Dananjaya; A.A. Ketut Jayawarsa; A.A. Sri Purnami (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2019)
The writing of this thesis aims to find out exports, imports, exchange rate, and the inflation rate has an impact on foreign exchange reserves Indonesia either partially or simultaneous. This research using secondary data published Bank Indonesia and the Central Bureau of statistics includes data on foreign exchange reserves, exports, imports, exchange rate, and inflation data in the form of annual 1999-2018 period. The object of this research is the total foreign exchange reserves, exports, imports, exchange rate, and inflation. Analysis tools in this study is the analysis of multiple linear foreign exchange reserves as the dependent variable and independent variable: exports, imports, exchange rate, and inflation are processed using the SPSS program. The results of this study using two stages, the first stage of variable Import experience multicollinearity resulting in variable import issued, phase two showed significant influential variable export results and a positive exchange rate effect, variable significant and positive, and significant influential variable inflation and negatively to foreign exchange reserves. To the three variables export, exchange rate, and inflation together impact Indonesia foreign exchange reserves.